A prospective study of the incidence, associations and outcomes of ocular surface squamous neoplasia in the United Kingdom - Kiire, Christine A; Stewart, Rosalind M K; Srinivasan, Sathish; Heimann, Heinrich; Kaye, Stephen B; Dhillon, Baljean (Eye (London), 2019)
To describe the incidence, associations and outcomes of ocular surface squamous neoplasia (OSSN) in the United Kingdom. Prospective, observational study of every new case of OSSN reported via the British Ophthalmological Surveillance Unit reporting scheme over a 12-month period. Cases were followed up for 12 months. The reported incidence of OSSN was 0.53 cases/million/year (conjunctival intraepithelial neoplasia: 0.43 cases/million/year; squamous cell carcinoma: 0.08 cases/million/year). Eighty-five per cent of affected patients were male, 97% were Caucasian, and the mean age at presentation was 67.9 (±12.8) years. Information on potential underlying risk factors was frequently unknown. The most commonly affected sites were the limbus and the nasal and temporal bulbar conjunctivae. Most patients presented with a visual acuity of 6/9 or better, without symptoms of pain or visual loss. Excision (with or without additional treatment) was the most common first-line treatment and interferon (with or without additional treatment) was the most common second-line treatment, although management varied widely. Complications of treatment were rare but occasionally severe. Recurrence within 12 months of follow-up occurred in at least 6% of patients. Although subject to reporting bias, these data suggest that there has not been a significant change in the incidence of OSSN in the United Kingdom, or its demographic profile, since 1996. The broad range of management approaches identified in this study reflect a lack of consensus as to the optimal referral and treatment pathways.